2017
DOI: 10.4236/ojgas.2017.72007
|View full text |Cite
|
Sign up to set email alerts
|

Jejunostomy Feeding Tube Placement in Gastrectomy Procedures: A Systematic Review

Abstract: Many nutritional interventions have been developed to improve nutritional outcomes following upper gastrointestinal surgery. The aim of this systematic review was to investigate whether or not the routine use of intraoperative jejunostomy feeding tubes in partial and total gastrectomy procedures is warranted when assessing complications and nutritional benefits such as improved chemotherapy tolerance. An electronic search of MEDLINE, Web of Science, Embase and CINAHL databases was performed to identify studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
(24 reference statements)
2
4
0
Order By: Relevance
“…Jejunostomy tube feeding acts as a useful means of achieving nutritional targets for patients postoperatively, yet carries the risk of both minor and major tube-related complications. 7,8 This survey revealed that surgeons were more likely to insert a jejunostomy feeding tube intraoperatively in Ivor Lewis oesophagectomy procedures as compared to total gastrectomy procedures, a finding consistent with UK data, whereby 68% of oesophagectomy patients had a feeding jejunostomy inserted compared to only 33% of gastrectomy patients. 14 One potential explanation for the difference in practice between the two procedures could be that surgeons are more likely to insert a jejunostomy feeding tube in Ivor Lewis oesophagectomy procedures as a safety mechanism should the patient develop an anastomotic leak.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Jejunostomy tube feeding acts as a useful means of achieving nutritional targets for patients postoperatively, yet carries the risk of both minor and major tube-related complications. 7,8 This survey revealed that surgeons were more likely to insert a jejunostomy feeding tube intraoperatively in Ivor Lewis oesophagectomy procedures as compared to total gastrectomy procedures, a finding consistent with UK data, whereby 68% of oesophagectomy patients had a feeding jejunostomy inserted compared to only 33% of gastrectomy patients. 14 One potential explanation for the difference in practice between the two procedures could be that surgeons are more likely to insert a jejunostomy feeding tube in Ivor Lewis oesophagectomy procedures as a safety mechanism should the patient develop an anastomotic leak.…”
Section: Discussionsupporting
confidence: 80%
“…Jejunostomy tube feeding acts as a useful means of achieving nutritional targets for patients postoperatively, yet carries the risk of both minor and major tube‐related complications . This survey revealed that surgeons were more likely to insert a jejunostomy feeding tube intraoperatively in Ivor Lewis oesophagectomy procedures as compared to total gastrectomy procedures, a finding consistent with UK data, whereby 68% of oesophagectomy patients had a feeding jejunostomy inserted compared to only 33% of gastrectomy patients .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations